SELF DISCLOSURE PEKERJA SEKS KOMERSIAL LADY BOY DALAM APLIKASI TINDER DI KABUPATEN BADUNG, BALI - Pradevi, Rinjani; Sugiarica Joni, I Dewa Ayu; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium, 2020)
ABSTRACT As a tourist destination, Bali has an impact on the presence of entertainment needs for tourists, one of which is prostitution. It is clear in Bali that prostitution is now shifting to social media, furthermore sex workers are also ladyboy. One form of the social media that is commonly used is the Tinder. One of the important aspects in the use of social media is self- disclosure. Research in this area commonly uses descriptive qualitative research, with data collection techniques through interviews. The results showed that the informants in this study claimed to openly carry out their self-disclosure process. However, using an onion layer model, not all stages were passed by the informants. Informants in this study also experienced a process of de-penetration when their Tinder matches did not accept their identity as ladyboy. Physical appearance and communication strategies are key for informants to attract the attention of their Tinder matches. Keywords: Self-disclosure, ladyboy, social penetration, tinder.